PARÁMETROS MORFOMÉTRICOS TRABECULARES DEL HUESO MAXILAR MANDIBULAR EVALUADOS CON TOMOGRAFÍA COMPUTARIZADA DE HAZ CÓNICO EN SUJETOS NORMALES, CON BAJA MASA ÓSEA CON TRATAMIENTOS ESPECÍFICOS Y SIN ESTOS. ESTUDIO PRELIMINAR. - Avendaño, María E.; Zabala, Walther; Zeni, Susana (Actualizaciones en Osteología)
Introduction: antiresorptive treatments such as bisphosphonates and denosumab are widely used to prevent bone loss, although their effects on mandibular microarchitecture are not yet fully established. Cone-beam computed tomography allows a noninvasive evaluation of trabecular structure and may help detect early alterations associated with bone fragility or antiresorptive therapy. Materials and methods: preliminary study in 45 postmenopausal women (>55 years), classified into a control group with normal bone mineral density and groups with osteopenia or osteoporosis, according to the treatment received Standardized mandibular conebeam computed tomography scans were obtained, and three regions of interest were analyzed per patient. Trabecular thickness, trabecular separation, bone volume fraction, anisotropy, and connectivity were assessed using BoneJ (ImageJ). The Shapiro--Wilk test was applied, and depending on distribution, the T test or Mann--Whitney test was used (p<0.05). All participants provided informed consent. The study followed the Declaration of Helsinki and was approved by the corresponding ethics committee. Results: untreated osteopenic women showed lower trabecular thickness and connectivity and greater trabecular separation compared with the control group (p<0.05). Patients treated with calcium, vitamin D, or hormone therapy showed no significant differences compared with the control group. Both patients treated with BPs and those treated with DMAb exhibited greater trabecular thickness and connectivity than the untreated osteopenic group (p<0.05), reaching values similar to those observed in the control group. However, trabecular separation remained elevated in sin patients with osteopenia or osteoporosis, irrespective of the treatment received. Conclusion: cone-beam computed tomography identified mandibular microstructural changes associated with bone fragility and antiresorptive treatments. These findings suggest that this technique may be useful for the early detection of alterations with clinical implications for dental planning.